Plant Response to Environmental Gradient Mediated by Trait Through Ontogeny on Common Tree Species at Two Contrasting Habitats in Karst Forest of Southern Taiwan - Muhammad Abdullah; I Fang Sun (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
One of central goal in ecology is to understand how plants respond to environment and what kind of attributes that can be obtained with an easy way to interpret the complexity of nature, especially on vegetation response. Ecologists use functional traits to understand how plants respond to environmental changes. Plant species may have experienced different environmental conditions during their ontogeny. Thus, they may show different patterns of ontogenetic trait variation (OTV) as their response to different environmental condition. In this study, the relationship between trait variation on different habitat and across ontogenetic stages both on community and population levels were investigated. Five selected leaves traits (leaf area, specific leaf area, leaf thickness, leaf dry matter content, and leaf succulence) were examined to look at plant response along soil water content and light gap interception gradient in Kenting forest dynamics plot (KFDP), Southern Taiwan. Leaf area was the most varied trait across habitat and ontogeny. Leaf thickness reveals an opposite pattern compare to leaf area. Leaf dry matter content (LDMC) showed less variation either between or within species and across ontogeny. Shift of community responses on environmental gradient by trait through ontogeny showed that intraspecific variation is important to be considered in ecological study. The other important finding in this study was by only using mean species we can misleading in understanding of plant responses to the environmental gradient in order to their adaptation both across different habitat and ontogenetic stages.